An Efficient Metal-Free Oxidative Esterification and Amination of Benzyl C–H Bond - Liu, Saiwen (Molecules, 2020)
An esterification and amination of benzylic C–H bonds was developed by using 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) under metal- and iodide-free conditions. Both carboxylic acids and amines could be used as ideal coupling partners for the oxidative coupling reactions with various diarylmethanes. A close to equal amount of coupling reagents was enough to afford the product in good to high yields.